Printed circuit boards produced by assembling unit cells - CHOW, EUGENE M; LU, JENG PING (2010)
A method of forming an interconnect substrate (30) includes providing at least two unit cells (100,102), arranging the unit cells to form a desired circuit pattern, and joining the unit cells to form the interconnect substrate having the desired circuit pattern. A circuit substrate, has a desired circuit pattern on a substrate, the substrate made up of at least two unit cells having conductive lines electrically connected together.